The accuracy of predictions about progress of patients on a stroke unit. Issue 11 (November 1990) - Lincoln, N B; Jackson, J M; Edmans, J A; Walker, M F; Farrow, V M; Latham, A; Coombes, K
Abstract : The aim of the study was to check the accuracy of predictions about the factors which affect the progress, in physical abilities and activities of daily living, of patients admitted to a stroke unit. A series of 60 patients admitted consecutively to a stroke unit were assessed on tests of motor, functional and cognitive abilities at admission. On the basis of these assessments predictions were made about the abilities of the patients at discharge. Patients were assessed for level of motor abilities and activities of daily living at discharge and the accuracy of the predictions checked. Predictions were found to be significantly correlated with outcome but the relationships were not so close as to be useful for the clinical management of individual patients.